2016
DOI: 10.14800/ccm.1238
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs as regulators of connexin-43 expression

Abstract: Posttranscriptional regulation of the biosynthesis of connexins, the building blocks of gap junctional channels, may occur by modulation of connexin mRNA stability and translation. To date, few RNA binding proteins and micro-RNAs (miRNAs) affecting connexin expression are known. In recent years, it has become clear that epigenetic processes are also essentially involved in connexin gene expression. In this review, we summarize recent knowledge on regulation of connexin expression by transcription factors and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Likewise, in glioblastoma multiforme, it was observed that downregulation of Cx43 by miR-221/222 is implicated in invasiveness and disease progression (Hao et al, 2012). The level of downregulation has been associated with the degree of malignancy (Hao et al, 2012; Ye et al, 2016). Therefore, when U251 human glioblastoma cells were transfected with antisense oligonucleotides against miR-221/222, Cx43 expression was upregulated, and cellular communication through GJCs was restored (Hao et al, 2012).…”
Section: Modulation Of Connexins By Mirnasmentioning
confidence: 99%
“…Likewise, in glioblastoma multiforme, it was observed that downregulation of Cx43 by miR-221/222 is implicated in invasiveness and disease progression (Hao et al, 2012). The level of downregulation has been associated with the degree of malignancy (Hao et al, 2012; Ye et al, 2016). Therefore, when U251 human glioblastoma cells were transfected with antisense oligonucleotides against miR-221/222, Cx43 expression was upregulated, and cellular communication through GJCs was restored (Hao et al, 2012).…”
Section: Modulation Of Connexins By Mirnasmentioning
confidence: 99%